A seleção brasileira de conjuntos de ginástica rítmica: perfil de ginastas e treinadoras, estrutura técnica e administrativa e o habitus construído - Lourenço, Márcia Regina Aversani (2015)
The general objective of the present thesis was to analyze, through the discourse of gymnasts and coaches, the profile of the Brazilian National Group of Rhythmic Gymnastics members during the period from 1997 to 2012, their technical and administrative structures and the sporting built habitus. Based on the Scandinavian Model, the thesis is composed of three complete original articles that counted on the participation of twelve gymnasts and four active coaches on BNG within the period that comprises four complete Olympic cycles named in this study as cycles 1, 2, 3 and 4. The first and second study of descriptive nature aimed to identify the profile of BNG members, the selecting and discharge procedures of gymnasts and the hiring and dismissal processes of coaches through semi-structured interviews and specific questionnaire. The results point to a continuous process of selecting and dismissal of gymnasts, although without precise and well-designed procedures. As for the hiring and dismissal of coaches, there is an absence of pre-established procedures, either at the invitation or at the dismissal moment. The third article, also of the descriptive character, utilized semi-structured interviews aiming to register the procedures and behaviors of coaches as well as the administrative structure of BNG, pointing to the similarities and differences between the cycles. The results point to cycle 2 as the period that brought together the best conditions of the gymnasium, the abode and the alimentation provided to the gymnasts, besides better results, and cycles 1, 2 and 3 present very similar characteristics on technical structure with resemblance on physical and technical preparations, and differences on tactical preparation. As for the administrative organization, the coaches are the most responsible for leading the groups in all cycles, being the headquarter partners on 1, 2 and 3 cycles the local administrative managers, and in cycle 4 the Brazilian Gymnastic Confederation was the fully responsible. The fourth article aimed to identify the presence of sports habitus on GR BNG through the testimony technique of oral history method. As a result, it presents ten habitus of SBC, related to the team joining and leaving processes, command, personal overcoming in favor to the group, body weight and result maintenances, maturation, travel and study routines, intense acquaintanceship, sports show and sporting life continuity. In general, the cycle 2 was the one that brought together the best physical and technical conditions and the best results as well. Cycle 3 presented the most interesting structure for studies and international internships with results maintenance, and cycle 4 offered better administrative structure, although it registered significant falls in the FIG results ranking. The identification of habitus allowed developing a wider view of the social group thus contributing for a better understanding on how the structures complement themselves in attitudes, customs, actions and specific rituals of the actors.